STRATEGI TOYOTA MOTOR CORPORATION DALAM MEMPERBAIKI CITRA PERUSAHAAN DI CHINA PASCA RECALL TAHUN 2010 – 2012 - EKKY PRAMULIA PUTRA; SYAFRI HARTO (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
This paper will analyze the strategy of Toyota Motor Corporation as the largest automotive manufacturer that originated from Japan in increasing sales and its image in China . Since the end of 2008 . Toyota is committed to remain a brand that is recognized internationally in terms of both quality and quantity . However, various competition and expansion makes Toyota should be able to develop and implement new strategies in the management of the company . So is the case when Toyota compete with other automobile manufacturers in China .In analyzing the existing problems , the authors used qualitative research methods that are explanative . The approach used in this study is a qualitative approach . I also use the theory relating to the cases. The perspective that I use is a liberal perspective . The author uses a liberal perspective to understand the strategies used Toyota . This research would then use the group level of analysis . The theory used is the author of the theory of the International Organization Theory and Competitive Advantage Theory.in this paper , the authors have the following results toyota managed to improve their corporate image . In china post product recall in 2010 . Toyota hybrid car sales showed an increase in sales value.Keyword : toyota motor corporation, image, strategy, recall